Global Solutions of Nonlinear Schrodinger Equations (Journal of Partial Differential Equations, 2005)
In this paper we study the existence of global solutions to the Cauchy problem of nonlinear Schrödinger equation by establishing time weight function spaces and using the contraction mapping principle.
Keywords: Nonlinear Schrödinger equation; Cauchy problem; global solutions